BIBLIOMETRIC STUDY OF THE INDIAN JOURNAL OF SOCIAL WORK USING SCOPUS - Walde, Praful Manohar; Borkar, Vikas S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study provides a bibliometric analysis of the Indian Journal of Social Work 2000 to 2024. The SCOPUS database was used to export the research data for this study. A total 772 publications published during the research period analysed to identify the yearwise distribution of the article, most cited publications with h-index, find out document type, most prominent authors, most prominent country, most prominent organization/institute, authorship pattern, degree of collaborations. VOSViewer software was used for science mapping to display the distribution of occurrence of keywords and the co-citation of author networks.